2019
DOI: 10.3847/1538-4357/ab16f1
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetic Pressure Front Upstream of the Heliopause and the Heliosheath Magnetic Fields and Plasma, Observed during 2017

Abstract: Voyager 1 (V1), moving in the interstellar magnetic field, observed an increase in the daily averages of B beginning on day ≈346, 2016, rising to a local maximum on day ≈382, and declining nearly monotonically for the most part until day 720, measured from 2016.0. A pressure front was observed during a ≈35-day interval beginning on day 346, 2016. The pressure front observed by V1 was not a shock, although one might expect it to evolve into a shock. Voyager 2 (V2) observed the distant heliosheath during 2017. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 64 publications
2
27
0
Order By: Relevance
“…IBEX regularly observes time variation in the morphology of the globallydistributed flux (see e.g., Schwadron et al 2018 for the first 9 years of LOS-integrated pressure observations), and the Voyagers have a long history of measuring MIRs, GMIRs, and other transient disturbances in situ at their various locations through the heliosphere and beyond (e.g., McDonald et al 1981;Burlaga et al 1985;Gurnett et al 1993;Whang & Burlaga 1995;Burlaga & Ness 1998;Paularena et al 2001;Burlaga et al 2003;Richardson et al 2006;Webber et al 2009;Burlaga et al 2011;Luo et al 2011). In addition to the 2012 events used in this study, Voyager 2 observed several GMIRs and MIRs in the heliosheath from 2015 to 2018 (e.g., Burlaga et al 2018aBurlaga et al , 2019, and Voyager 1 measured larger, more extended GCR anisotropy episodes starting in 2015 (e.g., Rankin et al 2019) and 2018. Likewise, IBEX has now collected 10 years of data.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…IBEX regularly observes time variation in the morphology of the globallydistributed flux (see e.g., Schwadron et al 2018 for the first 9 years of LOS-integrated pressure observations), and the Voyagers have a long history of measuring MIRs, GMIRs, and other transient disturbances in situ at their various locations through the heliosphere and beyond (e.g., McDonald et al 1981;Burlaga et al 1985;Gurnett et al 1993;Whang & Burlaga 1995;Burlaga & Ness 1998;Paularena et al 2001;Burlaga et al 2003;Richardson et al 2006;Webber et al 2009;Burlaga et al 2011;Luo et al 2011). In addition to the 2012 events used in this study, Voyager 2 observed several GMIRs and MIRs in the heliosheath from 2015 to 2018 (e.g., Burlaga et al 2018aBurlaga et al , 2019, and Voyager 1 measured larger, more extended GCR anisotropy episodes starting in 2015 (e.g., Rankin et al 2019) and 2018. Likewise, IBEX has now collected 10 years of data.…”
Section: Discussionmentioning
confidence: 73%
“…The Plasma Wave (PWS) instrument detected several locally-generated electron plasma emissions, typically preceded by GCR intensity enhancements measured by the Cosmic Ray Subsystem (CRS) and Low Energy Charged Particle Instruments (LECP; Gurnett et al , 2015. Following these precursors, the magnetometer (MAG) reported several disturbances in the form of weak, quasi-perpendicular, laminar changes to the magnetic field Burlaga et al 2019). LECP and CRS additionally observed an unexpected anisotropy in the GCRs characterized by a time-varying depletion of particles with near 90° pitch angles (Krimigis et al 2013;Rankin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this paper is to present recent observations of a fourth major event in the VLISM, the 2020 event, to discuss the nature of this event, and to show that there was a density jump associated with the previous pressure front, pf1, identified by Burlaga et al (2019). The 2020 event, together with the previous three major events provide a relatively simple view of the structure in the VLISM as we shall show below.…”
Section: Introductionmentioning
confidence: 94%
“…A distinctly different feature, related to an increase in B moved past V1 in ∼35 days during 2017 (Burlaga et al 2019). The jump in B was 1.19, comparable to the jump in the second shock (1.13).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation